Core Java 2 - Horstmann, Cay S. (Sun Microsystems Press, 2001)
Ask any experienced Java programmer: Core Java delivers the real-world guidance you need to accomplish even the most challenging tasks. That's why it's been an international best seller for five straight years. Core Java 2, Volume 1 covers the fundamentals of Java 2, Standard Edition, Version 1.3 and includes completely revised discussions of object-oriented Java development, enhanced coverage of Swing user interface components, and much more.